American fly threatens Africa's animal life - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1990)
Experts are putting out urgent warnings about a southern American fly - the screw worm fly - which has appeared for the first time in the African continent in Libya as a sheep parasite, and which is threatening cattle, domestic animals, important...